Health Status of Teenage Girls Based on Nutritional Status Assessment and Cardiorespiratory Endurance (VO2Max) - Junita, Dini; Al Rahmad, Agus Hendra; Fajarna, Farah (Universitas Airlangga, 2024)
Adolescent health sometimes still receives less attention, even though this age group has a high level of vulnerability to various nutritional and health problems. This study aims to determine the health status of adolescent girls including hemoglobin status, hydration status, and cardiorespiratory endurance (VO2Max). Samples were taken using a total sampling technique with the criteria of not having a history of heart and lung disease, living in the girls' dormitory at Integrated Islamic High School Al-Fityan School Aceh in good health and being willing to be respondents, and 60 female students were obtained. Hemoglobin status was observed from the hemoglobin level in the blood sample, hydration status was defined based on the composition of body fluids as measured by Bioelectrical Impedance Analysis (BIA), VO2Max value was calculated from pulse per minute in resting conditions. Data obtained from each variable was presented descriptively and tested for correlation using the Pearson 95% test. Based on the research results, in general, the majority of respondents can be concluded to have good nutritional status and cardiorespiratory endurance. However, 28.3% of respondents were still found with abnormal nutritional status, abnormal hemoglobin status of 28.3%, dehydration of 43.3% and 33.3% had low cardiorespiratory endurance. This research cannot prove the relationship between hemoglobin status and hydration status on cardiorespiratory endurance (p-value > 0.05). Periodic health status checks are required through the school health unit involving the Community Health Center or health workers to overcome existing problems in these four health status parameters.